Tokoh Saridin dalam Pementasan Kethoprak Saridin Andum Waris: Representasi Kearifan Kritik Masyarakat Jawa Pesisir - Sukarjo Waluyo (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Several districts and cities in Central Java have begun to identify the richness of local history, art and culture to become regional icons. Pati Regency is currently starting to develop a discourse as